Understanding desiccation tolerance using the resurrection plant Boea hygrometrica as a model system - Mitra, Jayeeta; Xu, Guanghui; Wang, Bo; Li, Meijing; Deng, Xin (Frontiers in Plant Science, 2013)
Vegetative tissues of Boea hygrometrica, a member of the Gesneriaceae family, can tolerate severe water loss to desiccated state and fully recover upon rehydration. Unlike many other so called “resurrection plants,” the detached leaves of B. hygrometrica also possess the same level of capacity for desiccation tolerance (DT) as that of whole plant. B. hygrometrica is distributed widely from the tropics to northern temperate regions in East Asia and grows vigorously in areas around limestone rocks, where dehydration occurs frequently, rapidly, and profoundly. The properties of detached B. hygrometrica leaves and relative ease of culture have made it a useful system to study the adaptive mechanisms of DT. Extensive studies have been conducted to identify the physiological, cellular, and molecular mechanisms underlying DT in the last decade, including specific responses to water stress, such as cell wall folding and pigment-protein complex stabilizing in desiccated leaves. In this review, the insight into the structural, physiological, and biochemical, and molecular alterations that accompany the acquisition of DT in B. hygrometrica is described. Finally a future perspective is proposed, with an emphasis on the emerging regulatory roles of retroelements and histone modifications in the acquisition of DT, and the need of establishment of genome sequence database and high throughput techniques to identify novel regulators for fully understanding of the matrix of DT.